“Jordi Juan Riquer, el primer novelista de Ibiza. Metges… o traficants?, su única novela”. - Ortega Román, Juan José (Revista de Filología Románica, 2006)
On 2005 we have celebrate 100 years from the birthday of Jordi Juan Riquer, the first Ibiza’s romancier. Just a very small literary circle knows him and his opera, and even has been ignored several years by Catalanish Literature History. So, our purpose is to focus on his personality and his written production.